Identifying match sequence thresholds to mitigate physical decline during congested fixtures - Silva, H.; Menezes, P.; Errekagorri, I.; Nakamura, F.; Marcelino, R. (International Journal of Sports Medicine, 2025)
This study compares locomotor activities during matches with different recovery intervals (<72, 72-120, 121-168,>168 h), considering accumulated travel distances (0, 1-250, 251-1,000,>1,000 km) in the previous 3, 5, and 7 days, and match sequence during congested periods. Locomotor data were collected using a global navigation satellite system and included total distance, distance covered between 14-20, 20-25, 25-30, and>30 km/h, maximal speed, maximal accelerations and decelerations, and the number of accelerations and decelerations between 2 and 3 m/s2. Congested fixtures (<72 and 72-120 h) negatively affected locomotor activities compared to noncongested ones (>168 h), with players covering less total distance (p=0.026) and distance at 14-20 km/h (p=0.027) and performing fewer accelerations (p=0.001) and decelerations (p=0.022) between 2 and 3 m/s2. Additionally, interactions with accumulated kilometers traveled revealed that high accumulated distances in the days leading up to congested fixtures exacerbated reductions in locomotor performance (p<0.05). Analysis of specific cases of consecutive congested fixtures showed a decline in locomotor activities after three matches within<72 hours or four matches within<120 hours. These findings highlight the importance of managing fixture schedules and travel distances to optimize player performance and reduce the risk of injury during congested match periods, with limiting players to short match sequences potentially being beneficial.